Citizenship Project Model To Develop Pancasila Student Profile In Civic Education - Azwar, Idham; Sulha; Risa Haridza (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2025)
This study aims to outline the civic project model as a means to foster the Pancasila learner profile within Civic Education. Utilizing a qualitative approach, the research employs a literature review method, drawing from various sources such as books, journal articles, scientific magazines, news media, research reports, and curriculum documents. The research process involves several steps: preparing tools and materials, creating a working bibliography, organizing the research timeline, reviewing literature and taking notes, and finally, synthesizing and analyzing the findings.  The findings indicate that the civic project model is well-suited for cultivating the Pancasila learner profile in Civic Education. By implementing this model, students can effectively develop traits aligned with the Pancasila learner profile, including faith and piety, strong moral character, appreciation for global diversity, self-reliance, a spirit of cooperation, critical thinking, and creativity.